SCREENING FOR Biochemical ABNORMALITIES IN UROLITHIASIS PATIENTS - Orakzai, Nasir; Hanbury, Damian C; Farrington, Kenneth (Journal of Ayub Medical College Abbottabad, 2004)
Background: The significance of biochemical screening in stone formers has been a debated topic. This study was conducted to investigate the frequency of biochemical abnormalities in our urolithiasis patients and to compare the abnormality between the first time and recurrent stone formers so that this information would help in assessing the value of biochemical screening in our practice. Methods: Over a twenty-one month period, new and recurrent stone disease patients had one random blood specimen and two random 24-hour urine collections analysed for biochemical abnormalities. Serum was checked for calcium, urate, phosphate and creatinine. The urines were measured for volumes, calcium, oxalate, urate, citrate, cystine and pH. Results: Out of total of 113 patients, 83 (73%) had some urinary or blood abnormality. Highest number of abnormalities were in urine. Low volume 33 (39.76%), hypercalciuria 33 (39.76%) and hyperoxaluria 20 (24.1%) were the main urinary abnormalities. Elevated serum creatinine in 10 (12.05%) was commonest blood abnormality. Females had significantly higher frequencies of low urinary volume (48% vs 21%, p=0.001), hyperoxaluria (38% vs 11%, p=0.002) and hypocitraturia (37% vs 0%, p<0.001). There was no significant difference of abnormality rate between first time and recurrent stone formers. Conclusion: A high frequency of urinary biochemical abnormality and equal abnormality frequencies among first time and recurrent stone formers highlights the significance of biochemical screening even in cases of initial stone presentation. We feel such diagnostic evaluation would help in providing precise treatment and efficient prophylaxis. Key Words: Urinary Calculi, Hyperoxaluria, Hyperuricaemia, Citric acid, Oxalic acid, Creatinine.